2019
DOI: 10.1519/jsc.0000000000002302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Practical Blood Flow Restriction Training on Adolescent Lower-Body Strength

Abstract: The purpose of this study was to examine the effects of a practical blood flow restriction (BFR) training program on lower-body strength of high school weightlifters. Twenty-five students were divided into three groups. For six weeks, each group completed the same resistance training program with the exception of the parallel back squat exercise (2 days/week), which was different for each group. One group (HI) completed a traditional high load (≥65% 1RM) back squat protocol with three sets of low repetitions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…On the other hand, the current study demonstrated that a contrast training program using low-loads with BFR as a conditioning activity might provide an effective and equivalent positive influence on maximal strength compared to using high-loads for preadolescents athletes. Our results agree with the evidence from other previous studies employing low load BFR with other populations ( Loenneke et al, 2012b ; Yamanaka et al, 2012 ; Luebbers et al, 2019 ; Hansen et al, 2020 ) and high school adolescent weightlifters ( Mohamed et al, 2017 ; Luebbers et al, 2019 ). No side-effects (hazards or unbearable discomfort) were reported during the ten weeks of training, which implicates that LL-BFRE integrated into a contrast training sequence is effective and safe for young athletes’ strength development.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the current study demonstrated that a contrast training program using low-loads with BFR as a conditioning activity might provide an effective and equivalent positive influence on maximal strength compared to using high-loads for preadolescents athletes. Our results agree with the evidence from other previous studies employing low load BFR with other populations ( Loenneke et al, 2012b ; Yamanaka et al, 2012 ; Luebbers et al, 2019 ; Hansen et al, 2020 ) and high school adolescent weightlifters ( Mohamed et al, 2017 ; Luebbers et al, 2019 ). No side-effects (hazards or unbearable discomfort) were reported during the ten weeks of training, which implicates that LL-BFRE integrated into a contrast training sequence is effective and safe for young athletes’ strength development.…”
Section: Discussionsupporting
confidence: 93%
“…The use of lower limb LL blood flow restriction exercises (LL-BFRE) has proven to be an efficacious alternative to high-load exercises (HL-RE) when used alternately within the same week or alternating weekly ( Hansen et al, 2020 ). The employment of LL-BFRE can provide a less stressful stimulus on joints and tendons with a similar level of neuromuscular adaptations ( Luebbers et al, 2019 ). Some studies have reported that low-load resistance exercises (i.e., ∼30% 1 RM) with a high number of repetitions (12–30) ( Pope et al, 2013 ) in combination with BFR (LL-BFRE) are effective at increasing muscle mass and strength across a wide range of populations ( Loenneke et al, 2014 ; Loenneke et al, 2012b ; Centner and Lauber, 2020 ; Pearson and Hussain, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both groups had two supervised BFR-training sessions per week, as suggested by (Patterson et al, 2019). Each session lasted approximately 15 min, equating to an average workload of 30 min per week (Luebbers et al, 2019). We aimed for a between-training recovery of at least 1-2 days (Figure 2).…”
Section: Study Design and Training Protocolmentioning
confidence: 99%
“…However, there has been an increasing number of studies within the last decades demonstrating that low-intensity strength training with external blood-flow restriction (BFR) induces similar effects compared to resistance training with heavier loads (65 + % 1RM). For instance, significant improvements in muscle mass, strength, and fatigue resistance were reported (Loenneke and Pujol, 2009;Luebbers et al, 2019;Pignanelli et al, 2020). BFR-training is characterized by a short-term, external restriction of the blood flow of the exercising muscles during the training session (Loenneke, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the ischemia that occurs, the body secretes growth hormone as a mechanism of self-protection and thus removes lactic acid and also fat metabolism is activated [13][14][15]. In recent years, traditional training methods have been applied together with blood flow restriction training [16].…”
mentioning
confidence: 99%